Analisis Strategi Pemasaran Produk Alat Tulis pada Ud. H. Muslan Pulungan Kecamatan Panyabungan Kabupaten Mandailing Natal di Tengah Pandemi Covid-19 - Nasution, Siti Maryam; Ramadhani, Sri; Nasution, Annio Indah Lestari (Regress: Journal of Economics & Management, 2022)
Marketing strategy is a process that is able to deliver the organization/company to a large market opportunity to increase sales and achieve the expected advantage. Marketing strategy is also an important tool so that companies are able to win the competition and be able to survive, especially during the Covid-19 pandemic. The Covid-19 pandemic is not just a health catastrophe, it has caused economic chaos. The object of this research is UD. H. Muslan Pulungan. Therefore, the purpose of this research is to find out the marketing strategy of stationery products carried out by UD. H. Muslan Pulungan in the midst of the Covid-19 pandemic and to find out what is the most appropriate strategy to increase sales of stationery products at UD. H. Muslan Pulungan in the midst of the Covid-19 pandemic. This research method uses a descriptive qualitative research approach and then analyzed using SWOT analysis to find out what are the strengths, weaknesses, opportunities and threats of the company's marketing strategy. The results of this study indicate that UD. H. Muslan Pulungan has implemented a product, price, place and promotion marketing mix strategy before and during the Covid-19 pandemic. Based on the results of the SWOT analysis, the IFAS matrix score is 3.37, this indicates that UD. H. Muslan Pulungan is in a strong internal position and the EFAS matrix score is 3.38, this shows that UD.H. Muslan Pulungan responds to opportunities very well and tries to avoid the threats that come. The right marketing strategy to increase sales of stationery products on the Cartesian diagram shows the company's position in quadrant I, which is to support an aggressive strategy. This position is very profitable for UD. H. Muslan Pulungan. Where the company has the power so that it can take advantage of existing opportunities. The marketing strategy used by the company to increase sales is to take advantage of technological developments to provide complete and up-to-date products, maintain good relations with customers, and design stores as attractive as possible by utilizing technological developments to be able to attract customers.